1982
DOI: 10.1007/bf00915950
|View full text |Cite
|
Sign up to set email alerts
|

The stability of child behavior disorders: A one year test-retest study of Adelaide versions of the Conners teacher and parent rating scales

Abstract: The stability of children's disorders was studied, using Adelaide versions of the Conners teachers and parent rating scales, with 5- to 12-year-olds. Of the 20 scales, 14 had high or moderate test-retest stability over the 1-year interval. Most scales also showed discriminant validity over this time. All but 2 of the 14 stable scales gave moderate stability coefficients at each of three age levels. Three teacher scales (Conduct Problem, Socially Rejected, and Antisocial) gave very low stability for the younges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

1984
1984
2009
2009

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 12 publications
1
23
0
1
Order By: Relevance
“…Similarly, examination of the Lie and F scales from the PIC did not invalidate any parent-report profiles at either pretest, posttest, or follow-up. Second, in those instances where practice effects have been found on the Conners's Parent and Teacher Questionnaires, the test-retest interval has been extremely brief (Glow, Glow, & Rump, 1982;Milich, Roberts, Loney, & Caputo, 1980). As Glow et al (1982) and Milich et al (1980) pointed out, however, it is very unlikely that practice effects would occur over longer test-retest intervals, such as the 3-month interval in our study.…”
Section: Discussionmentioning
confidence: 76%
“…Similarly, examination of the Lie and F scales from the PIC did not invalidate any parent-report profiles at either pretest, posttest, or follow-up. Second, in those instances where practice effects have been found on the Conners's Parent and Teacher Questionnaires, the test-retest interval has been extremely brief (Glow, Glow, & Rump, 1982;Milich, Roberts, Loney, & Caputo, 1980). As Glow et al (1982) and Milich et al (1980) pointed out, however, it is very unlikely that practice effects would occur over longer test-retest intervals, such as the 3-month interval in our study.…”
Section: Discussionmentioning
confidence: 76%
“…Test-retest data indicate satisfactory stabihty and, according to Glow et al (1982), 11 of the 13 subscales showed high discriminant validity over I year. The standardization sample was based on 1454 South Australian primary school children.…”
Section: Methodsmentioning
confidence: 91%
“…It has good test-retest reliability; [41] and inter-rater reliability; [42] and has been shown to reliably discriminate normal children from behaviorally disordered children. [43] Three of the seven factors or subscales were utilized in the study: Oppositional Subscale (A); Anxious/Shy Subscale (D); and Psychosomatic Subscale (G).…”
Section: Methodsmentioning
confidence: 98%